The Logic of Knowledge in Philippians - Fields, David R. (My University, 2007)
In his letter to the Philippians, Paul seeks to equip the church with moral and intellectual abilities to exercise their knowledge of the gospel in the difficult circumstances in which they find themselves. He does this by providing Christ (Phil 2:5-11), as the paradigm for Christian behaviour and community life. Though Käsemann (1950) and Martin (1967) challenged the view that Christ acts as a moral example in this passage, this study argues that a paradigmatic reading of Phil 2:5-11 best suits the context of the passage and Paul's overarching purposes throughout the letter. Paul also provides three concrete examples of those who have learned to narrate their lives in Christ, namely, Timothy, Epaphroditus and himself. Paul uses these people as examples for the church to emulate. This study further argues that the metaphor of character best describe the theological ethics that Paul employs in this letter.
Keywords: Religion; Religion